CRISPR/Cas9 and Nanotechnology Pertinence in Agricultural Crop Refinement - Naik, Banavath Jayanna; Shimoga, Ganesh; Kim, Seong-Cheol; Manjulatha, Mekapogu; Subramanyam Reddy, Chinreddy; Palem, Ramasubba Reddy; Kumar, Manu; Kim, Sang-Youn; Lee, Soo-Hong (Frontiers in Plant Science, 2022)
The CRISPR/Cas9 (Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated protein 9) method is a versatile technique that can be applied in crop refinement. Currently, the main reasons for declining agricultural yield are global warming, low rainfall, biotic and abiotic stresses, in addition to soil fertility issues caused by the use of harmful chemicals as fertilizers/additives. The declining yields can lead to inadequate supply of nutritional food as per global demand. Grains and horticultural crops including fruits, vegetables, and ornamental plants are crucial in sustaining human life. Genomic editing using CRISPR/Cas9 and nanotechnology has numerous advantages in crop development. Improving crop production using transgenic-free CRISPR/Cas9 technology and produced fertilizers, pesticides, and boosters for plants by adopting nanotechnology-based protocols can essentially overcome the universal food scarcity. This review briefly gives an overview on the potential applications of CRISPR/Cas9 and nanotechnology-based methods in developing the cultivation of major agricultural crops. In addition, the limitations and major challenges of genome editing in grains, vegetables, and fruits have been discussed in detail by emphasizing its applications in crop refinement strategy.